TanDEM-X Mission Status: The Complete New Topography of the Earth - Zink, Manfred; Moreira, Alberto; Bachmann, Markus; Braeutigam, Benjamin; Fritz, Thomas; Hajnsek, Irena; Krieger, Gerhard; Wessel, Birgit (IEEE International Geoscience and Remote Sensing Symposium (IGARSS), 2016)
TanDEM-X (TerraSAR-X add-on for Digital Elevation Measurements) is an Earth observation radar mission that consists of a SAR interferometer built by two almost identical satellites flying in close formation [1]-[4]. With a typical separation between the satellites of 120 to 500 m a global Digital Elevation Model (DEM) with 2 m relative height accuracy at 12 m posting is being generated. While the main mission phase for DEM data acquisition has been finished in 2014, the processing of the global TanDEM-X DEM will be concluded in autumn 2016. Final DEMs are well within specifications and feature a low percentage of void areas. Following the DEM data acquisition the capabilities of this unique mission for new scientific application have been demonstrated. In the meantime the continuation of the joint TerraSAR-X/TanDEM-X mission was approved and will be dedicated to the generation of DEMs with even higher accuracy for selected areas and further scientific experiments.
DLR Import::2019-04-03
Keywords: bistatic SAR formation; global Digital Elevation Model (DEM); SAR interferometry; TanDEM-X